2007
DOI: 10.1002/ppsc.200601076
|View full text |Cite
|
Sign up to set email alerts
|

Agglomerate TiO2 Aerosol Dynamics at High Concentrations

Abstract: Primary and agglomerate particle dynamics are investigated for aerosol synthesis of titania at high solids concentrations that are typically used for its industrial scale manufacture. Particle formation and growth are simulated accounting for chemical reaction, coagulation and sintering. Process conditions are chosen so that the resulting primary and hard‐agglomerate sizes are comparable with commercial product specifications. Neglecting aerosol polydispersity, the evolution of the diameter of primary particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…The γ values calculated at different fractional volumes are plotted in Figure Langevin dynamics simulations performed by Heine and Pratsinis (2007a). A good agreement for the transition from dilute to dense regime at f ≤ 10% reasonably confirms the validity of the new approach.…”
Section: Quantitative Analysissupporting
confidence: 60%
See 1 more Smart Citation
“…The γ values calculated at different fractional volumes are plotted in Figure Langevin dynamics simulations performed by Heine and Pratsinis (2007a). A good agreement for the transition from dilute to dense regime at f ≤ 10% reasonably confirms the validity of the new approach.…”
Section: Quantitative Analysissupporting
confidence: 60%
“…Such highly concentrated suspensions are well known in emulsions, where the droplet volume fraction may vary from zero to almost one (Bibette et al 1999) but can also be observed in aerosols. For example, a transition from dilute to dense (or concentrated) particle dynamics may take place during flame aerosol synthesis of nanostructured, fractal-like carbon black, fumed silica (Heine and Pratsinis 2006) or titania (Heine and Pratsinis 2007a) particles at industrially relevant conditions. Even though in such processes the particle volume fraction, f , is only 0.001-0.01%, depending on the process temperature, fractal-like silica agglomerates form and grow to occupy more than 10% of the gas volume during typical reactor residence times in the absence of restructuring or fragmentation (Heine and Pratsinis 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, agglomerate size and structure are affected and can influence the rheological properties of suspensions of these particles (Heine & Pratsinis, 2006, 2007a. The influence of high particle concentration on coagulation and even gelation has been discussed in several theoretical studies over the past years.…”
Section: Introductionmentioning
confidence: 95%
“…Corrections to that have been developed for van der Waals forces, charged or non-spherical particles (Friedlander, 2000) and other particle interactions (Seinfeld & Pandis, 2006) without altering, however, its basic theoretical framework: establishment of a steady-state Fickian flux to the colliding particle surface. By definition, the Smoluchowski equation cannot describe coagulation at high particle concentrations (effective volume fraction above 1%) that are encountered in large scale aerosol synthesis of fumed silica and titania (Heine & Pratsinis, 2006, 2007a as well as alumina, carbon black or soot (Sorensen, Hageman, Rush, Huang, & Oh, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…To minimize fusion or necking of the TiO 2 particles and formation of large hard agglomerates (or aggregates), their temperature has to be reduced to less than 600ºC (Mezey, 1966). Titania particles leaving the oxidizer (flame aerosol reactor) are typically soft agglomerates, several micrometers in diameter, consisting of smaller (about 500 nm) hard agglomerates (aggregates) that contain even smaller (about 200 nm) primary particles (Heine & Pratsinis, 2007). As a result, special milling (grinding) is used to break up the soft agglomerates before feeding them to the finishing plant where their surfaces are coated and conditioned for suspension in paints or compounding in polymer or paper matrixes.…”
Section: Titania Tiomentioning
confidence: 99%